Determination of fresh bean breeding lines improved by Black Sea Agricultural Research Institute and some commercial cultivars for resistance to Bean common mosaic virus (BCMV) - İlyas DELİGÖZ; Sevcan SARI; Onur KARAAĞAÇ (Derim, 2015)
Bean common mosaic virus (BCMV) is among the most destructive viruses in bean growing areas in the world. Using resistant cultivars is one of the most effective methods for virus control as there is no chemical treatment against BCMV in practice. Yield reductions due to BCMV may be up to 80% if susceptible bean cultivars are grown. In this study, 41 breeding lines improved by Black Sea Agricultural Research Institute (BSARI) and 31 commercial cultivars were tested for resistance levels to BCMV. For this purpose, NL-4 strain of BCMV was inoculated by the sap onto the leaves of bean plants with five replications. According to symptomatic assessments made 21 days after inoculation and the data from DAS-ELISA, the resistance levels of the all breeding lines were evaluated. The results showed that 29 breeding lines and 24 commercial cultivars were resistant to BCMV. In conclusion, the resistant breeding lines might be registered and used in the future to supply the source of virus-resistant seed after evaluating them in terms of yield and quality. The resistant cultivars determined in this study could be in breeding studies confidently.